Sri Lanka - Poverty Assessment : Engendering Growth with Equity, Opportunities and Challenges - World Bank (Washington, DC, 2012)
This report on poverty assessment in Sri Lanka establishes that the development story in Sri Lanka is one of mixed success. The country is on par with middle income countries and Millennium Development Goal timetables for universal primary school enrollment, gender parity in primary and secondary school enrollment, and universal provision of reproductive health services. At the same time, consumption income poverty persists and the poor continue to face basic welfare challenges such as malnutrition. A number of interrelated constraints prevent access by the poor to opportunities in more dynamic sectors of the economy. In poor rural areas and the estates economic and geographic constraints include inadequate connectivity to markets and growth centers, lack of electricity and transport facilities (infrastructure) and poor quality schools (public services). In poor urban areas constraints include inadequate access to clean water, electricity, sanitation and quality of housing. At the household level, the report assesses the cyclical nature of poverty traps caused by low levels of education, poor nutrition and underemployment (mostly associated with the informal sector). Population in the estates, North and East, and the tsunami-affected coastal areas are more likely to fall into the poverty trap cycle due to historical disadvantages or recent events like civil conflict or natural disasters. The report is organized as follows: Chapter 1 presents the Sri Lankan economy in an international context. Chapter 2 focuses on poverty, inequality and vulnerability. Chapter 3 profiles poor households and lagging regions. Chapter 4 discusses internal migration, remittances and urban concentration. Chapter 5 analyzes the human development challenges and the poverty nexus. Chapter 6 talks about the rural challenge in terms of raising agricultural productivity and non-farm incomes. Chapter 7 dissects the social and economic situation in the conflict-affected areas in the north and east, while Chapter 8 concludes with the an analysis of the poverty traps in the estates and the way forward.